The Impacts of National Rebirth Programme on the Moral Character of Nigerian Civil Service Employees (1999 a 2011): Akwa Ibom State Perspective (Global Journal of Human-Social Science, 2016)
This study examines the National Rebirth Programme with a view to determine the extent to which it has affected the attitude and behaviour patterns of Nigerians with special emphasis on Akwa Ibom State civil servants. The study's objectives were to investigate the impact of the National Rebirth Programme on the moral character of civil service employees in Akwa Ibom State, to find out whether the programme has engendered efficiency in service delivery in the state civil service and to recommend ways of making the programme more responsive, effective and relevant. The study adopted the qualitative and quantitative research methods and utilized data from both the primary and secondary sources which were analyzed within the context of structural functional theory. The findings of the study revealed that prior to the commencement of Obasanjo's administration in 1999, Nigerian civil/public service was plagued by moral decadence, inefficiency and poor attitude to work. Moreover, the study revealed that the civil service that was supposed to be the engine room of the system was not spared as vices such as corruption, indiscipline, and other related parochial considerations became prevalent in place of meritocracy, diligence and accountability.
Keywords: accountability; civil service; efficiency; ethics; national rebirth; service delivery